2012
DOI: 10.1161/strokeaha.112.667865
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation and the Risk of Ischemic Stroke

Abstract: Background and Purpose-Atrial fibrillation (AF) is an independent risk factor for stroke. Recent studies have demonstrated that the CHA 2 DS 2 -VASc scheme is useful for selecting patients who are truly at low risk. The goal of the present study was to compare the risk of ischemic stroke among AF patients with a CHA 2 DS 2 -VASc score of 0 (male) or 1 (female) with those without AF. Methods-The study enrolled 509 males (CHA 2 DS 2 -VASc scoreϭ0) and 320 females (CHA 2 DS 2 -VASc scoreϭ1) with AF who did not re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…Occurrence of lone AF probably does not increase the risk of stroke in younger people. Young patients with documented AF but without known vascular risk factors had the same rates of stroke as healthy controls [20]. These data suggest that thromboembolic risk may be triggered by something more than just the arrhythmia.…”
Section: Introductionmentioning
confidence: 65%
“…Occurrence of lone AF probably does not increase the risk of stroke in younger people. Young patients with documented AF but without known vascular risk factors had the same rates of stroke as healthy controls [20]. These data suggest that thromboembolic risk may be triggered by something more than just the arrhythmia.…”
Section: Introductionmentioning
confidence: 65%
“…More recently, a nationwide cohort study in Taiwan further demonstrated that AF males with a CHA 2 DS 2 -VASc score of 0 have a truly low-risk for stroke, which was similar to that of non-AF patients (1.6 versus 1.6 %, p-value: 0.92) during a follow-up of 57.4 ± 35.7 months. 24 In the same study, the annual stroke rate was around 0.92 % for AF females with a CHA 2 DS 2 -VASc score of 1 (only 1.45 % per year for dabigatran 150 mg). 25 It should be emphasised that the bleeding risk in RE-LY is under ideal, clinical trial circumstances, and the bleeding rate could probably be even higher in real life.…”
Section: The Usefulness Of the Cha 2 Ds 2 -Vasc Score In Identifying mentioning
confidence: 86%
“…4 ± 35.7 months. 24 In the same study, the annual stroke rate was around 0.92 % for AF females with a CHA 2 DS 2 -VASc score of 1 (only due to gender), 24 which was lower than that of life-threatening bleeding of dabigatran use in the Randomized Evaluation of Long Term Anticoagulant Therapy (RE-LY) study (1.22 % per year for dabigatran 110 milligrams [mg]; …”
mentioning
confidence: 98%
“…Of note, current European Society of Cardiology (ESC) guidelines 27 recommend considering women with AF without any other risk factor for stroke as having a global risk score of 0, so they should not assume any antithrombotic therapy. However, recently, a study by Chao et al 28 questioned this assumption: the authors enrolled 509 males (CHA 2 DS 2 -VASc score 0) and 320 females (CHA 2 DS 2 -VASc score 1) with AF, who were not receiving, according to guidelines, any antithrombotic therapy and matched control subjects without AF and any comorbidity from CHA 2 DS 2 -VASc (mean age 45 years). During the followup, 128 patients (1.4%) experienced ischemic stroke but, while the event rate did not differ between groups with and without AF for male patients (1.6% versus 1.6%; P=0.920), AF resulted in a significant risk factor for ischemic stroke among females (hazard ratio, 7.77), with event rates of 4.4% and 0.7% for female patients with and without AF (P,0.001).…”
Section: Common Risk Factors For Strokementioning
confidence: 99%